Reciprocal Changes of Circulating Long Non-Coding RNAs ZFAS1 and CDR1AS Predict Acute Myocardial Infarction - Zhang, Ying; Sun, Lihua; Xuan, Lina; Pan, Zhenwei; Li, Kang; Liu, Shuangshuang; Huang, Yuechao; Zhao, Xuyun; Huang, Lihua; Wang, Zhiguo; Hou, Yan; Li, Junnan; et al. (Scientific reports, 2016)
This study sought to evaluate the potential of circulating long non-coding RNAs (lncRNAs) as biomarkers for acute myocardial infarction (AMI). We measured the circulating levels of 15 individual lncRNAs, known to be relevant to cardiovascular disease, using the whole blood samples collected from 103 AMI patients, 149 non-AMI subjects and 95 healthy volunteers. We found that only two of them, Zinc finger antisense 1 ( ZFAS1 ) and Cdr1 antisense ( CDR1AS ), showed significant differential expression between AMI patients and control subjects. Circulating level of ZFAS1 was significantly lower in AMI (0.74 ± 0.07) than in non-AMI subjects (1.0 ± 0.05, P < 0.0001), whereas CDR1AS showed the opposite changes with its blood level markedly higher in AMI (2.18 ± 0.24) than in non-AMI subjects (1.0 ± 0.05, P < 0.0001). When comparison was made between AMI and non-AMI, the area under ROC curve was 0.664 for ZFAS1 alone or 0.671 for CDR1AS alone and 0.691 for ZFAS1 and CDR1AS combination. Univariate and multivariate analyses identified these two lncRNAs as independent predictors for AMI. Similar changes of circulating ZFAS1 and CDR1AS were consistently observed in an AMI mouse model. Reciprocal changes of circulating ZFAS1 and CDR1AS independently predict AMI and may be considered novel biomarkers of AMI.